Resilience of Outstanding Athlete with Serious Injury (Study of Athlets Tapak Suci Branch 14 South Jakarta) - Ahrul Azumar; Sokhivah Sokhivah; Ati Kusmawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Severe injury is a problem that is often experienced by athletes in achieving an achievement, so the emergence of severe injuries in athletes can cause the psychological condition of athletes to feel anxious, angry, depressed, and lack confidence. So that there is a need for resilience in athletes in order to change the response or psychological assessment of the athlete to the condition experienced and realize the individual qualities of the athlete who can develop in the face of suffering and can again continue to excel. This study aims to describe resilience in outstanding athletes who experience severe injuries. The research method uses qualitative methods with data retrieval techniques using in-depth interviews. Determination of informants using the Purposive Sampling technique, namely outstanding athletes who suffer severe injuries. The results of the study explained that the resilience of athletes who suffered severe injuries had a resilience process consisting of emotional regulation, implus control, optimism, self-efficacy and reaching out. So that athlete informants do not set rigid limits on their abilities. This means that athlete informants do not avoid a failure, but dare to face it to achieve a goal. It was also found that the resilience process of athletes who suffered severe injuries was influenced by the support of family, friends and coaches. However, it was found that the most dominant support factor affecting the resilience of outstanding athletes, namely from family factors derived from parents. This factor ultimately makes athletes form resilience characteristics to continue to excel again. such as social competence, problem-solving skills, autonomy, and awareness of future goals.